Plan of insertion of the objective boa-faith principle in contractual relations - Monte, Eriverton Resende (2022)
The present research addresses the principle of objective good faith, which was positivized in the Consumer Protection Code of 1990 and the Civil Code of 2002, integrating a wide range of principles foreseen in contractual relations, such as the principles of the dignity of the human person, solidarity, social function, among others. In this sense, the following question arises: does the application of the principle of objective good faith lie at the infraconstitutional and / or constitutional level? In order to answer this question, the general objective of the research is to demonstrate the level of this principle, if provided for in an infraconstitutional norm, such as the Civil Code and the Consumer Defense Code, or, if in addition to these, is included in the Federal Constitution of 1988. The study is justified by the need to discuss the constitutionalisation in private relations, and therefore the use of the principle of objective good faith in the contractual world, so that these legal relationships are formed, fulfilled and extinguished, compliance with the production of the desired effects by the parties and community, without forgetting the indispensability of the contracts to society. Regarding the methodology, the use of the inductive method, in a descriptive and analytical way, with bibliographical research, registration and judicial decisions, is attentive. Based on the fact that contractual relations became part of the phenomenon of depatrialization, the expected result lies in proposing a discussion of a reduction in the value of property in the past, in order to reach the value of the human person in correlation with good faith.